2021
DOI: 10.1007/s00261-021-03130-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional imaging findings of splenic infections: is differential diagnosis possible?

Abstract: The spleen plays an important role in the immunological homeostasis of the body. Several neoplastic and non-neoplastic diseases may affect this organ, and imaging is of fundamental importance for diagnosis. Infectious diseases of the spleen can be encountered in daily radiology practice, and differential diagnosis may sometimes be challenging. Infectious involvement of the spleen can be primary or secondary to a different source outside the spleen. Despite the fact that different infectious diseases may cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…The understanding of splenic function has continued to develop in recent centuries, and numerous diseases are known to affect this solid organ. One rare form of splenic pathology is abscess [ 2 , 3 ].…”
mentioning
confidence: 99%
“…The understanding of splenic function has continued to develop in recent centuries, and numerous diseases are known to affect this solid organ. One rare form of splenic pathology is abscess [ 2 , 3 ].…”
mentioning
confidence: 99%
“…19 It should be noted, however, that these imaging findings may also closely resemble sarcoidosis, candidiasis, and advanced metastatic disease. 15,20 Therefore, it is crucial to consider diagnoses other than CSD by examining coronary artery lesions and verifying the accompanying findings because KD and malignancy can result in severe outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several cases of atypical CSD that mimic other diseases have been reported in the literature. Other etiologies include metastatic tumors, 15 Epstein-Barr virus infection, 16 and autoimmune diseases. 17 Kara et al reported a suspected case of CSD neuroretinitis, which was eventually diagnosed as systemic lupus erythematosus based on a positive result for antinuclear antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid cysts can also resemble some rare calcifications caused by tuberculosis (Azzaza et al, 2020), but this also tends to generate multiple calcifications with a different morphology (Biehler‐Gomez et al, 2020; Gawne‐Cain & Hansell, 1996). The morphology of calcified abscesses observed in rare cases of brucellosis infection is also very distinct, showing a characteristic snowflake shape or, less commonly, a concentric lamellar pattern with central calcification (Colmenero et al, 2002; Karaosmanoglu et al, 2021; Torres et al, 2015). Fungal infections such as histoplamosis or Pneumocystis carinii can also originate calcifications, but these are multiple and smaller (Consul et al, 2020).…”
Section: Discussionmentioning
confidence: 99%